الصفحة النفسية لأساليب التفکير المُتناقضة لدى طلبة الدبلوم المهني ذوي الفراغ الفکري - فاطمة محمود الزيات (Faculty of Education - Port Said University, 2022)
هدف البحث إلى تعّرف الصفحة النفسية لأساليب التفکير المُتناقضة لدى طلبة الدبلوم المهني ذوي الفراغ الفکري، و تم اختيار عينة البحث من 25 طالب وطالبة من طلبة الدبلوم المهني المُلتحقين بکلية التربية بتطبيق مقياس الفراغ الفکري على العّينة الکلية 120طالب بالدبلوم المهني تکونت ، وتراوحت متوسطات أعمارهم بين (25- 32)، وصممت الباحثة أداتين:مقياس الفراغ الفکري، ومقياس أساليب التفکير المُتناقضة ، وأکدت نتائج البحث على أن مستوى الفراغ الفکري فوق المتوسط لدى طلابهم ، وأن الصفحة النفسية لدى طلبة الدبلوم المهني ذوي الفراغ الفکري تتمثل في الخارجي ثم الداخلي ثم التقليدي وأخيرًا التحرري ، وأوصت الدراسة بتنمية أسلوب التفکير الداخلي لأنه أساس التعلم الذاتي واکتساب الخبرات والنمو المهني المُتخصص وهو ما يتطلبه سوق العمل .the sample of research consisted of 25 students professional diploma students with intellectual emptiness, They were selected by applying the intellectual vacuum scale from the total sample 120 students professional diploma, average age (25- 32). the researcher designed 2 tools:the measure of the contradictory styles of thinking , and the measure of intellectual emptiness, and The results of the research confirmed that the level of intellectual vacuum is above average among their studentsthe the and revealed the profile of contractdic styles thinking is represented by external, then internal, then traditional and finally liberal, and the study recommended the development of the method of internal thinking because it is the basis of self-learning and gaining experience and specialized professional growth, which is required by the labor market.